Angiopoietin‐like protein 2 renders colorectal cancer cells resistant to chemotherapy by activating spleen tyrosine kinase–phosphoinositide 3‐kinase‐dependent anti‐apoptotic signaling. Issue 12 (5th November 2014) - Horiguchi, Haruki; Endo, Motoyoshi; Miyamoto, Yuji; Sakamoto, Yasuo; Odagiri, Haruki; Masuda, Tetsuro; Kadomatsu, Tsuyoshi; Tanoue, Hironori; Motokawa, Ikuyo; Terada, Kazutoyo; Morioka, Masaki Suimye; Manabe, Ichiro; et al.
<x xml:space="preserve">Abstract</x> Angiopoietin‐like protein 2 (ANGPTL2) plays an important role in inflammatory carcinogenesis and tumor metastasis by activating tumor angiogenesis and tumor cell chemotaxis and invasiveness. However, it is unclear whether ANGPTL2 expression has an effect on tumor cell survival. Here, we explored that possibility by determining whether ANGPTL2 expression altered survival of human colorectal cancer cell lines treated with antineoplastic drugs. To do so, we generated SW480 cells expressing ANGPTL2 (SW480/ANGPTL2) and control (SW480/Ctrl) cells. Apoptosis induced by antineoplastic drug treatment was significantly decreased in SW480/ANGPTL2 compared to control cells. Expression of anti‐apoptotic BCL‐2 family genes was upregulated in SW480/ANGPTL2 compared to SW480/Ctrl cells. To assess signaling downstream of ANGPTL2 underlying this effect, we carried out RNA sequencing analysis of SW480/ANGPTL2 and SW480/Ctrl cells. That analysis, combined with in vitro experiments, indicated that Syk‐PI3K signaling induced expression of BCL‐2 family genes in SW480/ANGPTL2 cells. Furthermore, ANGPTL2 increased its own expression in a feedback loop by activating the spleen tyrosine kinase–nuclear factor of activated T cells (Syk–NFAT) pathway. Finally, we observed a correlation between higher ANGPTL2 expression in primary unresectable tumors from colorectal cancer patients who underwent chemotherapy with a lower objective response rate. These findings suggest that attenuating ANGPTL2 signaling in tumor cells may block tumor cell resistance to antineoplastic therapies.